Biomass estimation in a boreal forest from TanDEM-X data, lidar DTM, and the interferometric water cloud model - Askne, Jan; Soja, Maciej; Ulander, Lars (Remote Sensing of Environment, 2017)
The semi-empirical Interferometric Water Cloud Model, IWCM, is used to estimate above ground forest biomass, AGB, in northern Sweden, Krycklan (64 degrees N 20 degrees E). The results are based on separate analysis of 14 TanDEM-X ac-quisitions from 2011 to 2014 and a Lidar digital terrain model (DTM). 29 stands covering 272 ha and with AGB 1 ha covering 3166 ha and with AGB